Transforming learning collabarative learning for a problem centered approach - Dewitt, Dorothy; Norlidah Alias; Saedah Siraj (University Of Malaya Press, 2015)
This book is also suitable for teachers, trainers and teacher-trainees to identify strategies and activities using technology to train leaners for the implementation of collaborative problem solving environment to promote higher order thinking